2013
DOI: 10.1016/j.antiviral.2012.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Shape of vaginal suppositories affects willingness-to-try and preference

Abstract: HIV and other sexually transmitted infections (STIs) are a global threat to public health that may be countered, in part, by microbicides. A successful microbicide must be both biologically efficacious and highly acceptable to users. Sensory attributes have a direct influence on product acceptability. We created a series of vaginal suppositories appropriate for use as microbicides to investigate the influence of shape on women's willingness-to-try. The influence of perceived size and firmness on acceptability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 26 publications
(28 reference statements)
1
34
0
Order By: Relevance
“…Women (Test 1: n = 99 and Test 2: n = 94) were recruited as described elsewhere [36, 37] to evaluate prototypes ex vivo (in their hands) at the Sensory Evaluation Center at Penn State. All participants met the following criteria for inclusion: a) female; b) between 18 and 55 years of age; c) reported having had vaginal sex with a man in the last 12 months; d) were willing to manipulate prototypes with their hands and evaluate them using a computer-guided assessment in an isolated test booth.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women (Test 1: n = 99 and Test 2: n = 94) were recruited as described elsewhere [36, 37] to evaluate prototypes ex vivo (in their hands) at the Sensory Evaluation Center at Penn State. All participants met the following criteria for inclusion: a) female; b) between 18 and 55 years of age; c) reported having had vaginal sex with a man in the last 12 months; d) were willing to manipulate prototypes with their hands and evaluate them using a computer-guided assessment in an isolated test booth.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to sample evaluation, participants were asked to watch a 90s video in which a female physician demonstrates how a participant should evaluate a prototype in her hand [36, 37]. Participants were instructed to: 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prepared suppositories had bullet shape, as shown in Figure 1, as this shape is considered preferable by women 33 . The results obtained with MTS assays, and the values of cytotoxicity concentration 50 (CC 50 ) are summarized in Figure 2, according to the different vaginal cell lines used.…”
Section: Preparation Of Vaginal Suppositories and Cytotoxicity Assay mentioning
confidence: 99%
“…Hayes and colleagues measured ex vivo acceptability of oval-shaped products (ovules) or suppositories and a hypothetical applicator by assessing user willingness-to-try, perceived effectiveness, and imagined ease of insertion [61]. In a preceding focus group study, the authors identified that most women preferred a long oval and bullet shape compared to tear drop, tampon, or round oval shapes [62]. By systematically varying the size (1, 3, and, 5 g) and firmness as measured by storage modulus, nine different products were prepared.…”
Section: Design Considerations For On-demand Productsmentioning
confidence: 99%